Development of E-Worksheet Characterized by PBL Model Integrated with 21st Century Skills to Improve Students' Science Process Skills - Nuraisa Nuraisa; Muslimin Muslimin; Sahrul Saehana; Darsikin Darsikin; Unggul Wahyono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to produce e-worksheet with characteristics of PBL model integrated with 21st century skills that are effective to improve students' science process skills and critical thinking skills. This type of research is development research (Research and Development), with the ADDIE development model. The population and sample of the study were all students of class VIII A at SMPN 4 Tanantovea. The research data collection technique was carried out using the LKS feasibility test through filling out a questionnaire by students, multiple choice tests to measure science process skills and essay tests to measure critical thinking skills given twice each, namely before learning (pretest) and after learning (posttest). The research data were analyzed descriptively using statistical applications. The results showed that the feasibility test of the LKS was categorized as very feasible with a score of 93%. The effectiveness of e-worksheet learning to improve students' science process skills is categorized as very large with d cohen's effect size of 2.61 and critical thinking skills are also in the very large category with d cohen's effect size of 5.84. Based on the results of this study e-worksheet with the characteristics of the PBL model integrated with 21st century skills is feasible and useful for creating a generation of students who are more skilled, independent, and ready to contribute in an increasingly connected and complex global society. Students will bring the skills needed to innovate, solve problems, and collaborate effectively, making them future leaders capable of facing challenges that have not been seen before.